Kicking against the PRCs - A Domesticated Transposase Antagonises Silencing Mediated by Polycomb Group Proteins and Is an Accessory Component of Polycomb Repressive Complex 2. - Shih Chieh Liang; Ben Hartwig; Pumi Perera; Santiago Mora-García; Erica de Leau; Harry Thornton; Flavia de Lima Alves; Juri Rappsilber; Suxin Yang; Geo Velikkakam James; Korbinian Schneeberger; E Jean Finnegan; et al. (PLoS Genetics)
The Polycomb group (PcG) and trithorax group (trxG) genes play crucial roles in development by regulating expression of homeotic and other genes controlling cell fate. Both groups catalyse modifications of chromatin, particularly histone methylation, leading to epigenetic changes that affect gene activity. The trxG antagonizes the function of PcG genes by activating PcG target genes, and consequently trxG mutants suppress PcG mutant phenotypes. We previously identified the ANTAGONIST OF LIKE HETEROCHROMATIN PROTEIN1 (ALP1) gene as a genetic suppressor of mutants in the Arabidopsis PcG gene LIKE HETEROCHROMATIN PROTEIN1 (LHP1). Here, we show that ALP1 interacts genetically with several other PcG and trxG components and that it antagonizes PcG silencing. Transcriptional profiling reveals that when PcG activity is compromised numerous target genes are hyper-activated in seedlings and that in most cases this requires ALP1. Furthermore, when PcG activity is present ALP1 is needed for full activation of several floral homeotic genes that are repressed by the PcG. Strikingly, ALP1 does not encode a known chromatin protein but rather a protein related to PIF/Harbinger class transposases. Phylogenetic analysis indicates that ALP1 is broadly conserved in land plants and likely lost transposase activity and acquired a novel function during angiosperm evolution. Consistent with this, immunoprecipitation and mass spectrometry (IP-MS) show that ALP1 associates, in vivo, with core components of POLYCOMB REPRESSIVE COMPLEX 2 (PRC2), a widely conserved PcG protein complex which functions as a H3K27me3 histone methyltransferase. Furthermore, in reciprocal pulldowns using the histone methyltransferase CURLY LEAF (CLF), we identify not only ALP1 and the core PRC2 components but also plant-specific accessory components including EMBRYONIC FLOWER 1 (EMF1), a transcriptional repressor previously associated with PRC1-like complexes. Taken together our data suggest that ALP1 inhibits PcG silencing by blocking the interaction of the core PRC2 with accessory components that promote its HMTase activity or its role in inhibiting transcription. ALP1 is the first example of a domesticated transposase acquiring a novel function as a PcG component. The antagonistic interaction of a modified transposase with the PcG machinery is novel and may have arisen as a means for the cognate transposon to evade host surveillance or for the host to exploit features of the transposition machinery beneficial for epigenetic regulation of gene activity.